Prioritizing partners and products for the sustainability of the EU’s agri-food trade - Zinngrebe, Yves; Berger, Jurij; Bunn, Christian; Felipe-Lucia, María R.; Graßnick, Nina; Kastner, Thomas; Pe’er, Guy; Schleyer, Christian; Lakner, Sebastian (Elsevier, 2024)
Global agri-food systems couple sustainability challenges in producing countries to consumption behavior and regulations in destination markets. We assume that trade relations can be prioritized according to (1) the relevance (share of imports) and (2) leverage (share of domestic production for destination market). This study analyzes the relevance and leverage of the EU’s crop imports in monetary values, footprints, and defor estation. Our results identify high relevance and leverage values in trade relations with specific partner coun tries, particularly palm oil and rubber specialists in East Asia and soy-producing MERCOSUR countries. High leverage values in imports from African-Caribbean-Pacific small sugar specialists and other small countries highlight the EU’s potential to establish sustainability criteria. We suggest that the EU revises incoherent foreign and domestic policies and proactively engages with trading partners to include sustainability safe guards in the whole value chain with particular focus on trade relations with high relevance and leverage values.